The Role of Blockchain in Digital Content Copyright - Alfin Kurniawan; Elya Elya; Bayu Wibisana (Universitas Islam Al-Azhar Mataram, 2025)
The rapid advancement of digital technology has significantly transformed content distribution and consumption patterns while simultaneously increasing the vulnerability to digital copyright infringement. This article explores the application of blockchain technology as a strategic solution for protecting digital content copyright, particularly in the Indonesian context. Utilizing a literature review method, the study investigates key blockchain features transparency, decentralization, immutability, and smart contract automation that enhance the integrity and security of intellectual property rights management. Blockchain enables the permanent and tamper-proof recording of content ownership and creation timestamps, while also facilitating automated royalty distribution without third-party intervention. These capabilities make blockchain an efficient mechanism for copyright verification and real-time rights tracking. However, blockchain adoption in Indonesia still faces significant challenges, including limited digital literacy among creative industry actors, inadequate technological infrastructure, and the absence of clear legal frameworks supporting its implementation in the field of intellectual property rights. The study also highlights initial initiatives across various sectors, such as education, music, and digital art, where blockchain has been employed to secure content through NFTs and decentralized copyright registration platforms. Findings emphasize the need for multi-sector collaboration, the establishment of supportive regulations, and technological education to ensure the successful implementation of blockchain-based copyright systems. Overall, blockchain has the potential to serve as a transformative pillar in developing a fairer, more transparent, and sustainable copyright protection ecosystem in the digital era.